A prática da escrita para além do copismo no 5º ano do ensino fundamental: uma mediação sob as lentes dos estudos do letramento - Albuquerque, Adenailde Maria Soares de (2024)
This research, situated in the area of Applied Linguistics, has as its object of study the writing practices mobilized to intervene in the training of students who are copyists/copyists within the literacy process in a literacy context. Copyism, in this work, is understood as a pedagogically obsolete practice that opposes writing as a social practice. The interest in contributing to the advancement of writing proficiency based on socially situated writing practices and a literacy process in a literacy context originated from concerns about teaching practices in the initial years of Elementary School (EF) and from reflections on the difficulties that children in public schools face in learning to read and write. Thus, the research was guided by a question: how to develop more significant pedagogical practices, within the literacy and literacy process, to intervene in the training of students who are merely copyists? Therefore, the general objective of the research is to analyze socially situated writing practices as alternatives to intervention in the training of students who are merely copyists in order to make them proficient writers. The following theoretical-methodological perspectives were used: Vygotsky's (1987) sociocultural learning theories and Piaget's constructivist theories, in addition to the propositions of Freire (2001, 1967, 2011); Street (2014); Kleiman (2016, 1995, 2024); Tfouni (1988); Geraldi (2002); Soares (1996, 2020, 2021, 2023); among others. This is an applied action research, with a qualitative and interventionist approach. The research participants were 5th grade EF students from a public school in the municipal network in Santa Rita/PB. The research was developed based on two methodological stages, the first referring to the text genre of culinary recipes and the second to the text genre of toy instruction manuals. We used participant observation, discussion groups and pedagogical workshops as data-generating instruments. Data analysis considered the students' textual productions based on the analysis categories listed to guide situated writing practices: Text composition form, Linguistic and semiotic analysis (orthography) and Autonomous writing. The importance of introducing socially situated practices of written language use into the classroom was noted, of teaching literacy by starting from the text and returning to it. It was from the understanding of the production context, the reflection on deviations and their causes (orthography) that we were able to monitor changes in the way students perceived the texts and their production, that is, this study demonstrated that socially situated writing practices developed from pedagogical workshops, creative and systematized strategies can enhance more autonomous and meaningful writing.